Validity of near‐infrared light transillumination for the assessment of proximal caries in permanent teeth. (3rd November 2021) - Wang, F; Su, C; Yang, C; von den Hoff, JW; Bian, Z; Meng, L
Abstract: Purpose: The aim of this study was to evaluate the performance of DIAGNOcam (DC) in diagnosing proximal caries and to compare its effectiveness with the International Caries Detection and Assessment System (ICDAS) and bitewing radiography (BWR). Methods: 118 premolars extracted for orthodontic reasons were included and examined using three detection methods and validated by histological sections as the gold standard. The sensitivity, specificity and areas under the ROC curve (Az value) at the outer half enamel (D1), inner half enamel (D2) and dentine (D3) thresholds were compared between different methods. Results: At all categories, the specificity of DC was almost as high as ICDAS and BWR. DC showed a significantly higher sensitivity (0.68) than both visual (0.33) and radiographic examination (0.47) at the D1 threshold. DC presented the highest Az value (area under the ROC curve) at the D1 and D2 threshold (0.81, 0.86), while BWR showed the greatest Az values at D3 (0.94). Furthermore, DC had the highest association strength with the gold standard (Spearman's ρ = 0.80). Conclusions: It can be concluded that DC could detect proximal caries effectively and showed comparable or even better performance than ICDAS and BWR.